Using self-paced reading in research with heritage speakers: a role for reading skill in the online processing of Spanish verb argument specifications - Jegerski, Jill; Keating, Gregory D. (Frontiers in Psychology, 2023)
Relatively little is known about how heritage speakers process language in real time, despite recent calls for the use of online methods such as self-paced reading, eyetracking, and ERPs (event-related potentials) in research on this early bilingual population. The present study addressed this gap with an empirical study of the online processing of heritage speakers of Spanish in the U.S. using self-paced reading, which is the online method that is most accessible to a wide body of researchers because it does not require specialized equipment. The processing target was related to the online integration of verb argument specifications, which was chosen because it does not involve ungrammatical sentences and therefore may be less likely to involve metalinguistic knowledge and less likely to put heritage speakers at a disadvantage than measures that rely on the recognition of grammatical errors. More specifically, this study examined an effect that occurs when a noun phrase appears after an intransitive verb, which can cause processing difficulty relative to a comparison condition in which the verb is transitive. The participants were 58 heritage speakers of Spanish and a comparison group of 16 first-generation immigrants raised in Spanish-speaking countries. Both groups showed the expected transitivity effect on the post-verbal noun phrase during self-paced reading, but the heritage speaker group also showed a spillover effect on the post-critical region. Among the heritage speakers, these effects were associated with lower self-ratings for reading skill in Spanish and with slower average reading speed during the experiment. Three theoretical accounts of the apparent susceptibility to spillover effects among heritage speakers are proposed: that it is a characteristic of shallow processing, that it is due to underdeveloped reading skill, and that it is an artifact of the self-paced reading method. The latter two possibilities are especially consistent with a role for reading skill in these results.